Synthetic integrin antibodies discovered by yeast display reveal αV subunit pairing preferences with β subunits - Yuxin Hao; Jiabin Yan; Courtney Fraser; Aiping Jiang; Murali Anuganti; Roushu Zhang; Kenneth Lloyd; Joseph Jardine; Jessica Coppola; Rob Meijers; Jing Li; Timothy A. Springer (Taylor & Francis Group, 2024)
Integrins are cell surface receptors that mediate the interactions of cells with their surroundings and play essential roles in cell adhesion, migration, and homeostasis. Eight of the 24 integrins bind to the tripeptide Arg-Gly-Asp (RGD) motif in their extracellular ligands, comprising the RGD-binding integrin subfamily. Despite similarity in recognizing the RGD motif and some redundancy, these integrins can selectively recognize RGD-containing ligands to fulfill specific functions in cellular processes. Antibodies against individual RGD-binding integrins are desirable for investigating their specific functions, and were selected here from a synthetic yeast-displayed Fab library. We discovered 11 antibodies that exhibit high specificity and affinity toward their target integrins, i.e. αVβ3, αVβ5, αVβ6, αVβ8, and α5β1. Of these, six are function-blocking antibodies and contain a ligand-mimetic R(G/L/T)D motif in their CDR3 sequences. We report antibody-binding specificity, kinetics, and binding affinity for purified integrin ectodomains, as well as intact integrins on the cell surface. We further used these antibodies to reveal binding preferences of the αV subunit for its 5 β-subunit partners: β6 = β8 > β3 > β1 = β5.